Melatonin Supplementation Decreases Aerobic Exercise Training Induced-Lipid Peroxidation and Malondialdehyde in Sedentary Young Women - Ziaadini Fatemeh; Aminae Mohsen; Mahsa Rastegar M.M.; Abbasian Sadegh; Memari Amir Hossein (Polish Journal of Food and Nutrition Sciences)
Five percent of consumed oxygen produces a number of reactive oxygen species (ROS) including free radicals and other chemical products such as malondialdehyde (MDA). MDA increases lipid peroxidation such as low density lipoproteins cholesterol (LDL-c). Melatonin can decrease MDA and lipid peroxidation, but there are limited data about melatonin supplementation on MDA and lipid peroxidation of women. So the aim of this study was to evaluate the effects of melatonin supplementation on exercise-induced MDA and lipid peroxidation of sedentary young women. Twenty sedentary young (20–25 years old) women were selected and randomly divided into two exercise training-supplement (n=10) and exercise training (n=10) groups. Pretest/posttest body mass, BMI, rest heart rate (RHR), body fat percent, menstrual cycle, blood sampling for MDA and lipid profile were collected. Aerobic exercise training was performed for 8 weeks, triple weekly. Melatonin supplementation was ingested at 3 mg/day for exercise training-supplement. Results showed that the long term exercise training increased MDA concentrations, and melatonin supplementation significantly suppressed MDA surge (−25.2±2.87; 95% CI=−30.91 to −19.49). Moreover, post-exercise training LDL-c levels significantly declined due to melatonin supplementation in sedentary young women (19.5±2.41; 95% CI=12.272 to 25.728). We concluded that 3 mg melatonin supplementation following aerobic exercise training would attenuate ROS and improve lipid profile of young sedentary women.